2016
DOI: 10.4186/ej.2016.20.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Identifying Black Spots Based on Potential Saving in Accident Costs

Abstract: Abstract. In improving road safety, the identification of black spots based on potential saving in accident costs is an attempt to make the selection of black spots to treat out of the identified ones. This selection is based on a new approach in which safety potential is employed as a key parameter which has a dual function of identification and prioritization. With this approach, it is possible to find black spots where safety improvement measures are expected to have the greatest economical effectiveness. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This is due to the independence of this parameter, which can be collected easily through an investigation without calculations or predictions. The suggested period for identification is a range between 3 and 5 years (Nguyen et al, 2016). The road analysis will focus on road sections determined based on the sliding window method, which allows dividing a road into sections to find the number of accidents in each.…”
Section: Black Spot Definition and Identification In European And Other Countriesmentioning
confidence: 99%
“…This is due to the independence of this parameter, which can be collected easily through an investigation without calculations or predictions. The suggested period for identification is a range between 3 and 5 years (Nguyen et al, 2016). The road analysis will focus on road sections determined based on the sliding window method, which allows dividing a road into sections to find the number of accidents in each.…”
Section: Black Spot Definition and Identification In European And Other Countriesmentioning
confidence: 99%
“…urban intersections [2]. This accident-prone location, usually called blackspots or hotspots, covers where safety improvement measures are expected to have the greatest economic effectiveness [3]. Some studies show, focusing on Black spot road safety interventions could decrease the rate of accidents up to 28% [4].…”
Section: Imentioning
confidence: 99%
“…More modern approaches were shown appeared when Ambros et al identified of hazardous locations in regional road network by comparison of reactive and proactive approaches [12]. Nguyen et al addressed an approach towards identification of black spots based on saving road costs [13]. Rouhi and Behzadi managed to prioritize four conventional methods, namely those based on frequency, rate, severity, and rate-severity, and proposed a hybrid method using AHP [14].…”
Section: Introductionmentioning
confidence: 99%